(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2009)
Reactive oxygen species (ROS) and free radical species have been implicated in initiating or accompanying many diseases in living organisms; there is thus, a continual need for antioxidants molecules to inactivate ROS/free radicals. Many studies of plants crude extracts have demonstrated free-radical scavenging and antioxidant action. Salacia species have long been used, in several countries, as traditional medicines against certain diseases and for their anti-inflammatory properties. In this study, Salacia campestris Walp (Hippocrateaceae) root bark ethanol extract (ScEtOH) was assessed for its ability to scavenge free radicals and reactive oxygen species; the results were expressed as percentage inhibition of the active species. ScEtOH was efficient against studied species: DPPH radical (obtained inhibition = 30%), ABTS+ (IC50 = 1.8±0.8 μg/mL), HOCl (IC50 = 1.7 ± 0.1 μg/mL), O2- (obtained inhibition = 32%), and NO (obtained inhibition = 18 %). Peroxidase activity inhibition was evaluated through the guaiacol oxidation reaction catalyzed by hemin, HRP and myeloperoxidase (MPO); data showed that ScEtOH at 10 μg/mL led to 54 and 51% of inhibition, respectively, for the hemin and HRP systems. In the MPO system, ScEtOH promoted a 50% inhibition at 8.9 μg/mL, whereas quercetin, a powerful MPO inhibitor, inhibited this system at 1.35 μg/mL.